2023
DOI: 10.1159/000530685
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine Attenuates Radiation-Induced Ototoxicity in a Rat Model

Abstract: <b><i>Introduction:</i></b> Tetramethylpyrazine (TMP) is a chemical compound, which has been shown to possess numerous biological features such as anticoagulation, inhibition of platelet aggregation, anti-inflammation, capillary dilatation, improvement in microcirculation, and protection against reactive oxygen radicals. The aim of the present study was to investigate the protective effect of TMP against radiation-induced ototoxicity. <b><i>Materials and Methods:</i>&l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…[53] Studies have shown that NF-κB is activated by cochlear radiation and reaches its maximum activation state after 2-6 h. Tetramethylpyridine has anti-inflammatory and anticoagulant effects that protect against radiation-induced ototoxicity. [54,55] In addition, hereditary hearing loss has recently been associated with inflammation. [56][57][58] While the pathogenesis of SNHL is unclear and incomplete, inflammation is a critical component in the pathogenesis of many SNHLs.…”
Section: Other Snhlsmentioning
confidence: 99%
“…[53] Studies have shown that NF-κB is activated by cochlear radiation and reaches its maximum activation state after 2-6 h. Tetramethylpyridine has anti-inflammatory and anticoagulant effects that protect against radiation-induced ototoxicity. [54,55] In addition, hereditary hearing loss has recently been associated with inflammation. [56][57][58] While the pathogenesis of SNHL is unclear and incomplete, inflammation is a critical component in the pathogenesis of many SNHLs.…”
Section: Other Snhlsmentioning
confidence: 99%